Reportable irregularities and audit quality: Insights from South Africa. Issue 1 (March 2015) - Maroun, Warren
Highlights The research provides one of the first interpretive accounts of auditing in an African setting. The association between audit quality and a duty to report irregularities to an independent regulatory body is explored. The reporting duty contributes to the perceived auditor independence. It also emphasises the importance of engagement leader participation and sound consultation and review policies. Issuing more than a generic audit report can add significantly to the perceived value of the assurance function.